The Influence of Social Media (Instagram) of Bantul’s General Election Commissions on Voters Participation in the 2019 Elections - Agus Priyanto; Eko Priyo Purnomo; Mochammad Iqbal Fadhlurrohman; Herry fahamsyah; Etika Khairina (Universitas Muhammadiyah Tangerang, 2021)
In 2019 social media has indeed become a familiar phenomenon for Indonesian people in general. Social media is a communication tool that cannot be abandoned by every individual. In fact, it has become a habit for every individual to share information through social media, because the practical benefits of social media are a means of communication. Social media in its use has many benefits, both positive and negative, like two ends of the sword. The positive value of social media is used as a means of communication, a means of sharing information for voters, and a means of socializing between the KPU and the public. This study uses a qualitative descriptive method by describing the data obtained from the General Election Commission (KPU) of Bantul Regency by analyzing data taken directly from the documents of the General Election Commission of Bantul Regency (KPU Bantul). Voter Participation in Bantul Regency shows a higher participation rate compared to participation in the 2014 Election. The difference between the 2014 and 2019 Elections lies in the number of voters. In 2014 Facebook was used while in 2019 it was using Instagram. The percentage of voter participation in 2019 showed 87.9% of the total number of voters, while in 2014 voter participation was only 81% (Republika.co.id). In the 2014 Election, the KPU did not use Instagram to disseminate information about the Election, while the 2019 Election showed good participation.Di tahun 2019 media sosial memang menjadi fenomena yang tidak asing lagi bagi masyarakat Indonesia pada umumnya. Media sosial merupakan alat komunikasi yang tidak bisa ditinggalkan oleh setiap individu. Bahkan sudah menjadi kebiasaan setiap individu untuk berbagi informasi melalui media sosial, karena manfaat praktis media sosial adalah sebagai sarana komunikasi.Media sosial dalam penggunaannya memiliki banyak manfaat, baik positif maupun negatif, ibarat dua ujung pedang. Nilai positif media sosial digunakan sebagai sarana komunikasi, sarana berbagi informasi bagi pemilih, dan sarana sosialisasi antara KPU dengan masyarakat.Penelitian ini menggunakan metode deskriptif kualitatif dengan mendeskripsikan data yang diperoleh dari dokumen Komisi Pemilihan Umum (KPU) Kabupaten Bantul dengan menganalisis data yang diambil langsung dari dokumen Komisi Pemilihan Umum Kabupaten Bantul (KPU Bantul). Partisipasi Pemilih di Kabupaten Bantul menunjukkan angka partisipasi yang lebih tinggi dibandingkan dengan partisipasi pada Pemilu 2014. Perbedaan Pemilu 2014 dan 2019 terletak pada jumlah pemilih. Pada tahun 2014 Facebook digunakan sedangkan pada tahun 2019 menggunakan Instagram. Persentase partisipasi pemilih pada 2019 menunjukkan 87,9% dari total jumlah pemilih, sedangkan pada 2014 partisipasi pemilih hanya 81% (Republika.co.id). Pada Pemilu 2014, KPU tidak menggunakan Instagram untuk menyebarluaskan informasi seputar Pemilu, sedangkan Pemilu 2019 menunjukkan partisipasi yang baik.